USING MOBILE APPLICATIONS TO IDENTIFY THE PROFESSIONAL ABILITIES OF APPLICANTS - Barannyk, М.; Sheykina, N.; Bazdyrov, О.; Zhovtonishko, І. (Physical and Mathematical Education, 2021)
Formulation of the problem. The article is devoted to the study of the possibilities of mobile application using for the analysis of professional abilities of applicants for higher education. Mobile applications, as an integral part of mobile technology, are one of the leading places in terms of the frequency of human use of information technology in everyday life. The development and implementation of such software in the educational process, and especially the career guidance of future entrants, is becoming increasingly important in today's world of digital and interactive learning technologies. In this article the main methods of professional orientation diagnostics were analyzed and structured, the market of vocational mobile applications was analyzed, a new platform was proposed, which has an opportunity to take into account the emotional component of entrants when passing vocational testing, which significantly affects test results. Most of the applications that exist today and are used to identify the professional abilities of applicants are presented in the form of a questionnaire and do not take into account the emotional component of the person currently being tested. The authors offer a mobile application that takes into account the emotional state of the applicant during the professional-oriented testing, which contributes to the choice and success in the future profession.Materials and methods. In this research theoretical methods were used, in particular: systematic analysis of scientific sources and normative documents, analysis of methods and technologies of mobile applications development.Results. As a result of research on the example of the developed Toolhoo platform, it was proposed to use mobile applications as an effective tool for propensity testing to a particular specialty for future university entrants.This article analyzes and structures the main methods of diagnostics of professional orientation, analyzes the market of career guidance mobile applications, developed and proposed a new platform that can take into account the emotional component of applicants in professional testing, which significantly affects the test results.Conclusions. Mobile applications are used in all areas of human life, and as a result, the market of mobile applications is developing at an incredible rate. The study shows that the mobile application is a fast and convenient way to pass vocational testing for applicants. Authors offer the use of a new mobile platform that takes into account the emotional state of university entrants during questioning.
Keywords: mobile applications; professional abilities; entrants; information technologies; career guidance